Ethnomathematics-Based Electronic Student Worksheets on Balinese Gringsing Woven Fabric with Sanan Empeg Motif in Mathematics Content of Flat Shapes Material - Ni Putu Intan Sukma Aryanti; I Made Suarjana; Ni Made Dainivitri Sinta Sari (Jurnal Ragam Pengabdian, 2026)
This study aims to develop an ethnomathematics-based electronic student worksheets on Balinese Gringsing Woven Fabric with Sanan Empeg motif. The subjects of this study were 6 experts, 50 fifth-grade elementary school students who participated in the instrument testing, and 20 fourth-grade elementary school students who applied ethnomathematics-based electronic student worksheets on Balinese Gringsing Woven Fabric with Sanan Empeg motif. The data analysis techniques used were qualitative descriptive analysis, quantitative descriptive statistical analysis, and inferential statistical analysis. The data collection methods used were observation, interviews, questionnaires or surveys, and tests. Based on analysis results, it was found that the validity test according to the learning material experts obtained an average of 3,82. Instructional design experts obtained an average of 3,91 and learning media experts obtained an average of 3,90 with a qualification of very worthy. The practicality of the product obtained an average individual trial assessment of 3,93 and small group trial average of 3,91 with a qualification of very practical. The significance value (2-tailed) in the correlated t-test showed a figure of 0,001 or p < 0,05 so that ethnomathematics-based electronic student worksheets on Balinese Gringsing Woven Fabric with Sanan Empeg motif was effective in improving learning outcomes in mathematics content on flat shapes for fourth-grade elementary school students. Based on these results, it can be concluded that ethnomathematics-based electronic student worksheets on Balinese Gringsing Woven Fabric with Sanan Empeg motif is valid, practical, and effective in improving student learning outcomes, making it suitable for continuous use in learning activities.